Scrotal Leiomyoma; anUnusual Cause for Scrotal Mass - DasNayak, Goutami; Pradhan, Prita; Rath, Jayasree; Kumar Badhai, Samit (Archives of Men’s Health, 2021)
Leiomyomas are the most common benign mesenchymal tumors arising from smooth muscle cells. Cutaneous leiomyoma constitutes small percentage of all the leiomyomas. However, genital leiomyomas, such as those of the scrotum have an even lower incidence rate. A 43-year-old man presented with complaints of a painless swelling in the left side of the scrotum. A clinical diagnosis of scrotal wall fibroma was made and the swelling was excised which had homogenous, grey-white areas with whorling and histologically showed features of leiomyoma. Here we present a rare cause of scrotal mass in a middle-aged man.